Progesterone hydroxylation by cytochromes P450 2C and 3A enzymes in marmoset liver microsomes. (3rd August 2018) - Nakanishi, Kazuyuki; Uehara, Shotaro; Uno, Yasuhiro; Inoue, Takashi; Sasaki, Erika; Yamazaki, Hiroshi
Abstract: 1. Common marmosets ( Callithrix jacchus ) are potentially useful nonhuman primate models for preclinical drug metabolism studies. However, the roles of marmoset cytochrome P450 (P450) isoforms in the oxidation of endobiotic progesterone have not been fully investigated. In this study, the roles of marmoset P450 isoforms in progesterone hydroxylation were extensively determined. 2. The activities of liver microsomes from individual marmosets with respect to progesterone 21/17α- and 16α/6β-hydroxylation were significantly correlated with those for flurbiprofen 4-hydroxylation and midazolam 1′-hydroxylation, respectively, as similar correlations have been found in humans. Anti-P450 2 C and 3 A antibodies suppressed progesterone 21/17α- and 16α/6β-hydroxylation, respectively, in marmoset liver microsomes. 3. Recombinant marmoset P450 2C58 and 2C19 catalyzed progesterone to form 21-hydroxyprogesterone and 16α-hydroxyprogesterone, respectively, as major products with high maximum velocity/ K m values of 0.53 and 0.089 mL/min/nmol, respectively. Recombinant marmoset P450 3A4/90 oxidized progesterone to form 6β-hydroxyprogesterone as a major product with homotropic cooperativity (>1 of Hill coefficients). 4. These results indicate that the overall activities and roles of liver microsomal P450 enzymes in marmoset livers are similar to those in humans, especially for progesterone 21/17α- and 16α/6β-hydroxylation by marmoset P450 2 C and 3 A enzymes, respectively, suggesting important roles for these P450 enzymes in the metabolism of endobiotics in marmosets.